Distinct steps in the adsorption of pulmonary surfactant to an air-liquid interface. - Walters, R W (2000)
To investigate the mechanisms by which vesicles of pulmonary surfactant adsorb to an air-liquid interface, we measured the effect of different phospholipids and of their concentration both in the subphase and at the interface on this process. Adsorbing vesicles contained the hydrophobic surfactant proteins mixed with the following four sets of surfactant phospholipids that varied the content of anionic headgroups and mixed acyl chains independently: the complete set of purified phospholipids (PPL) from calf surfactant; modified PPL (mPPL) from which the anionic phospholipids were removed; a mixture of dipalmitoyl phosphatidylcholine (DPPC) and dipalmitoyl phosphatidylglycerol (DPPG) (9:1, mol:mol); and DPPC alone. The initial reduction in surface tension depended strongly on the anionic phospholipids and the subphase concentration. The acyl groups had no effect. Adsorption beyond the initial stage depended more on the mixed acyl groups, became increasingly independent of subphase concentration, and was determined instead by the interfacial concentration of the surface film. The different constituents produced the same effects in vesicles adsorbing to a clean interface or in a preexisting film to which vesicles of SP:DPPC adsorbed. Adsorption for vesicles of SP:PPL adsorbing to DPPC or of SP:DPPC to PPL above a certain threshold surface concentration followed exactly the same isotherm. Our results fit best with a two-step model for adsorption. The anionic phospholipids first promote the initial juxtaposition of vesicles to the interface. Compounds with mixed acyl constituents at the point of contact between vesicle and interface then facilitate fusion with the surface.